Kissing Stents for Superior Vena Cava Syndrome Due to Mediastinal Fibrosis. (27th May 2018) - Bardet, Jérémy; Fabre, Dominique; Brenot, Philippe; Watkins, Claire; Fadel, Elie
Purpose: To report the endovascular reconstruction of the superior vena cava (SVC), innominate and internal jugular veins following stenosis due to mediastinal fibrosis. Case Report: A 36-year-old female with mediastinal fibrosis was referred for symptomatic SVC syndrome (SVCS). A covered stent was inserted in the SVC with 2 kissing stents in the innominate and jugular veins via anterograde right femoral vein access with sandwich technique. She exhibited near-immediate relief of debilitating symptoms. Computed tomographic scan demonstrated patent vessels at 1 year. Conclusions: Extensive endovascular venous reconstruction is an effective treatment for SVCS due to mediastinal fibrosis.